Mechanism for data recovery as a result of data corruption, infection and/or unauthorized modification - L. V. Cherkesova; V. A. Savelyev; E. A. Revyakina; A. R. Polulyakh; M. A. Sementsov (Вестник Дагестанского государственного технического университета: Технические науки, 2025)
Objective. The objective of the study is software analysis of hashing, compression and recovery methods and development of a software module on this basis.Method. Hashing algorithms were used in the study.Result. The possible functionality of the software tool and organized integrity checking mechanisms by using hash tables and restoring a file from a backup copy are presented. The software module uses the developed algorithm that allows eliminating vulnerabilities associated with program integrity, as well as significantly reducing the impact of malicious algorithms on file integrity. A comparative analysis with existing analogs is carried out for the developed software tool, as well as a graphical representation of the algorithm's performance, showing the dependence of time on the number of files. To develop the software module, a reversible incremental backup algorithm was chosen as the most suitable for the developed algorithm and more convenient to use.Conclusion. The proposed data recovery mechanism is a modern solution that ensures the safety of personal files in case of their damage. The main tasks for future improvement of the software tool have been defined: expanding the functionality of the software tool; optimizing the program code to achieve greater performance; updating and improving the software modules; adding disk image copy functions.